The Language of Hans Christian Andersen’s Fairy Tales – Compared with Earlier Tales - Lundskær-Nielsen, Tom (Scandinavistica Vilnensis, 2014)
It is my aim in this article to outline some of the main characteristics of Hans Christian Andersen’s language as used in the fairy tales. I shall concentrate on the earliest tales because this will allow me to focus on the radical linguistic departure from previous fairy tales that Andersen’s early work in this genre represents. Even so, comparisons apply not only to other writers; one of the most illuminating comparisons is with Andersen’s first attempt at fairy-tale writing, published in 1830.
Keywords: Hans Christian Andersen; language of fairy tales